Host and microbiota derived extracellular vesicles: Crucial players in iron homeostasis - Daou, Yasmeen; Falabrègue, Marion; Pourzand, Charareh; Peyssonnaux, Carole; Edeas, Marvin (Frontiers in Medicine, 2022)
Iron is a double-edged sword. It is vital for all that’s living, yet its deficiency or overload can be fatal. In humans, iron homeostasis is tightly regulated at both cellular and systemic levels. Extracellular vesicles (EVs), now known as major players in cellular communication, potentially play an important role in regulating iron metabolism. The gut microbiota was also recently reported to impact the iron metabolism process and indirectly participate in regulating iron homeostasis, yet there is no proof of whether or not microbiota-derived EVs interfere in this relationship. In this review, we discuss the implication of EVs on iron metabolism and homeostasis. We elaborate on the blooming role of gut microbiota in iron homeostasis while focusing on the possible EVs contribution. We conclude that EVs are extensively involved in the complex iron metabolism process; they carry ferritin and express transferrin receptors. Bone marrow-derived EVs even induce hepcidin expression in β-thalassemia. The gut microbiota, in turn, affects iron homeostasis on the level of iron absorption and possibly macrophage iron recycling, with still no proof of the interference of EVs. This review is the first step toward understanding the multiplex iron metabolism process. Targeting extracellular vesicles and gut microbiota-derived extracellular vesicles will be a huge challenge to treat many diseases related to iron metabolism alteration.